Literasi Digital Qur’ani: Integrasi Konsep Laghw dan Tadabbur dalam Menghadapi Brain Rot di Era Digital - Arsyad, Muhammad; Bashori, Bashori; Nadhiroh, Wardatun (UIN Sultan Syarif Kasim Riau, 2025)
This study aims to construct a digital literacy model grounded in Qur’anic epistemology as a response to the phenomenon of brain rot, defined as cognitive deterioration resulting from excessive exposure to superficial digital content. This issue presents a significant threat to the intellectual and spiritual well-being of society in the contemporary information age. Current digital literacy frameworks predominantly focus on technical competencies, often overlooking the epistemological and spiritual dimensions, thereby necessitating a more comprehensive and integrative approach. Employing a qualitative methodology based on library research and a descriptive-analytical approach, this study analyzes classical and contemporary Qur’anic exegeses (tafsīr) related to the concepts of Laghw (futility) and Tadabbur (deep reflection). These concepts are critically examined through an interdisciplinary lens incorporating insights from neuroscience, psychology, and media studies. The findings indicate that Laghw provides a diagnostic framework for understanding the cognitive and spiritual underpinnings of brain rot, whereas Tadabbur offers an epistemic remedy aimed at revitalizing reflective thought and enhancing self-regulation. The integration of these concepts culminates in the formulation of the “Qur’anic Digital Literacy Model,” which is structured around three fundamental pillars: Tabayyun Digital (information verification), Adab Digital (digital ethics), and Mujāhadah al-Nafs (self-restraint). This model aspires to cultivate the Ulu al-Albab personality type individuals who exemplify both knowledge and virtue. Theoretically, this framework contributes to the discourse on digital literacy from an Islamic epistemological perspective; practically, it offers actionable strategies for educators, parents, and individuals to promote healthier and more meaningful interactions with digital technology.Abstrak: Penelitian ini bertujuan mengonstruksi model literasi digital yang berakar pada epistemologi Qur’ani untuk merespons fenomena brain rotyakni degradasi kognitif akibat paparan berlebihan terhadap konten digital yang dangkal. Fenomena ini menjadi ancaman serius bagi kualitas intelektual dan spiritual masyarakat di era informasi global. Pendekatan literasi digital yang ada sering kali hanya menekankan aspek teknis, tanpa menyentuh akar persoalan pada dimensi epistemologis dan spiritual, sehingga diperlukan paradigma alternatif yang lebih komprehensif. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka dengan pendekatan deskriptif-analitis. Analisis dilakukan terhadap korpus tafsir klasik dan kontemporer terkait konsep Laghw (kesia-siaan) dan Tadabbur (perenungan mendalam), kemudian didialogkan secara kritis dan interdisipliner dengan literatur modern dari bidang neurosains, psikologi, dan studi media. Hasil penelitian menunjukkan bahwa konsep Laghw dapat berfungsi sebagai kerangka diagnosis untuk memahami akar krisis kognitif dan spiritual dalam fenomena brain rot, sementara Tadabbur dapat difungsikan sebagai terapi epistemik untuk merevitalisasi daya pikir reflektif serta memperkuat regulasi diri. Sintesis dari kedua konsep ini melahirkan “Model Literasi Digital Qur’ani” yang terdiri dari tiga pilar utama: Tabayyun Digital (verifikasi informasi), Adab Digital (etika interaksi daring), dan Mujahadah an-Nafs (pengendalian diri). Model ini diarahkan untuk membentuk kepribadian Ulu al-Albab sebagai ideal manusia berpengetahuan dan berakhlak. Secara teoretis, model ini memperkaya wacana literasi digital berbasis nilai Islam, dan secara praktis memberikan panduan aplikatif bagi pendidik, orang tua, serta individu dalam membangun interaksi teknologi yang sehat dan bermakna.